The Effect Application of Desmodium ovalifolium Inoculated with Arbuscular Mycorrhizal Fungi on Octomeles sumatrana Miq. Seedling on Post Mining Soil - Sri Muryati; Irdika Mansur; Sri Wilarso Budi (Forest Tree Seed Technology Research & Development Center (FTSTRDC)/ Balai Penelitian dan, 2020)
Mining activities resulted on environmental degradation and ecosystem damage. Legume cover crop forming symbiosis with beneficial soil microorganism is widely well known to be used for degraded land reclamation such as in post mining area. Desmodium spp. is one of legume cover crop forming symbiosis with arbuscular mycorrhizal fungi (AMF) and rhizobium. This study aimed: (1) to isolate and characterize AMF collected from rhizosfer of 4 species of Desmodium spp. grow in gold mining of PT. Cibaliung Sumberdaya, Banten; (2) to study the growth of Octomeles sumatrana planted together with D. ovalifolium inoculated with AMF. Soil collected from post mining was used as growth media. There were two factors in this study: AMF inoculation and compost treatments. Based on morphological characteristics after culture breeding , there were 23 spesies of Glomus sp. and 3 spesies of Acaulospora sp. isolated from 4 spesies of Desmodium spp. collected in PT. Cibaliung Sumberdaya. Inoculation of AMF and compost application increased height of O. sumatrana in two weeks after planting. Single inoculation of AMF into O. sumatrana improved height and increased number of spore as well. Combination of compost with post mining soil had the highest increased in height, diameter, total biomass, roots biomass, and sprout biomass of O. sumatrana.